How Preoperative Motor Weakness Affects the Extent of Recovery After Elective Spine Surgery in Patients with Degenerative Lumbar Spinal Stenosis. Issue 16 (15th August 2021) - Yagi, Mitsuru; Suzuki, Satoshi; Nori, Satoshi; Okada, Eijiro; Tsuji, Osahiko; Nagoshi, Narihito; Nakamura, Masaya; Matsumoto, Morio; Watanabe, Kota
Abstract : Study Design: Retrospective review. Objective: This study sought to determine how baseline motor weakness (MW) affects elective spine surgery in patients with degenerative lumbar spinal stenosis (LSS). Summary of Background Data: Favorable clinical outcomes have been described for elective spine surgery in patients with LSS. However, the way preoperative MW affects the patient's health-related quality of life (HRQoL) after surgery is not well understood. Methods: A retrospective review of prospectively collected data from 305 surgically treated patients with LSS who had 2-year follow-up was performed (age 71 ± 9 yrs, male 62%). Demographic, radiographic, and clinical outcomes were analyzed at baseline and at 1-year, 2-year, and 3-year postoperation. The Japanese Orthopedic Association Back Pain Evaluation Questionnaire was used to assess the HRQoLs. The HRQoLs were compared between those with or without preop MW. Adjusted multivariate logistic regression analyses were performed to determine whether MW affected HRQoLs. Results: One hundred sixteen patients (38%) were categorized as MW+. The patient background including age, sex, presence of degenerative spondylolisthesis, type of surgery, and presence of neurological claudication were similar between the two groups. However, the 1-, 2-, and 3-year postoperative visual analogue scale of back pain, leg pain, leg numbness, the Japanese Orthopedic Association Back Pain Evaluation Questionnaire lumbar function, social life, mental health, and walking ability were all inferior in the MW+ group, whereas a similar percentage of patients achieved a minimum clinically important difference in all subdomains at 3 years. The adjusted multivariate logistic regression analyses showed that having ≥2 muscles with MW, and severity of MW (manual motor test grade) were independent risk factors for both difficulty climbing stairs and walking >15 minutes. (muscles with MW≥2; stair climbing: OR 6.4[2.3–17.4], walking: OR 3.2[1.4–7.3], severity of MW; stair climbing: OR 2.5[1.4–4.4], walking: OR 2.2[1.3–3.7]). Conclusion: The patients with baseline MW had inferior HRQoL for up to 3 years compared with that of those without MW; however, the amount of improvement in HRQoL was comparable. Timely follow-up is important to find out the deterioration of motor function. Level of Evidence: 4 Abstract : Supplemental Digital Content is available in the textA retrospective review of 305 surgically treated degenerative lumbar spinal stenosis from a single-center database was performed. The LS patients with preoperative motor weakness had remained disability not only on the pain and function but also influences on the mental health and social life after surgery, despite similar percentage of the patient achieved MCID of all of the subdomains. Surgery should be considered before the paralysis becomes severe.